2017
DOI: 10.1101/132373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple P450s and Variation in Neuronal Genes Underpins the Response to the Insecticide Imidacloprid in a Population ofDrosophila melanogaster

Abstract: Abstract:Insecticide resistance is an economically important example of evolution in response to intense selection pressure. Here, the genetics of resistance to the neonicotinoid insecticide imidacloprid is explored using the Drosophila Genetic Reference Panel, a collection of inbred Drosophila melanogaster genotypes derived from a single population in North Carolina. Imidacloprid resistance varied substantially among genotypes, and more resistant genotypes tended to show increased capacity to metabolize and e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Conversely, we only identified two genes belonging to the canonical detoxification genes family, and neither of these (Cyp311a1 and Cyp4s3) are strong candidates for having roles in insecticide metabolism. The P450 Cyp6g1, that has previously been associated with imidacloprid metabolism [62][63][64] , was not detected in our analysis and inspection of a SNP tagging the CNV believed to be causal for the resistance (2R:12185332), is fixed in almost all Australian populations (the exception being a South Australian population) and was at high frequency in the north American populations we sampled (0.71 to 0.97). The analysis of microbial "hologenomes" adds another likely contributor to the multifactorial basis to variation in insecticide mortality.…”
Section: Multifactorial Bases To Resistancementioning
confidence: 60%
“…Conversely, we only identified two genes belonging to the canonical detoxification genes family, and neither of these (Cyp311a1 and Cyp4s3) are strong candidates for having roles in insecticide metabolism. The P450 Cyp6g1, that has previously been associated with imidacloprid metabolism [62][63][64] , was not detected in our analysis and inspection of a SNP tagging the CNV believed to be causal for the resistance (2R:12185332), is fixed in almost all Australian populations (the exception being a South Australian population) and was at high frequency in the north American populations we sampled (0.71 to 0.97). The analysis of microbial "hologenomes" adds another likely contributor to the multifactorial basis to variation in insecticide mortality.…”
Section: Multifactorial Bases To Resistancementioning
confidence: 60%
“…33 Most recently, two P450s, Cyp6g1 and Cyp6g2, have been shown to contribute to the metabolization of imidacloprid and are involved in conferring resistance to this insecticide in D. melanogaster. 34 Additionally, multiple P450s associated with DDT resistance were over-transcribed in the highly DDT-resistant D. melanogaster strain as compared to DDT-susceptible strain, suggesting that resistance may be in part attributable to differential expression of multiple P450s. 35,36 Retention of a functional Nrf2/Maf (NF-E2-related factor 2/Muscle aponeurosis fibromatosis) transcription factor binding site was previously linked to the over-expression of Cyp6a2 associated with DDT resistance in 91-R, 37 as was trans-regulatory control by the D. melanogaster CNC-bZIP (Cap'n'collar-basic leucine zipper) transcription factor ortholog to Nrf2 that regulates the transcriptional response of several genes encoding detoxification enzymes that contain an upstream antioxidant response element (ARE), 38,39 including Cyp6a2 and Cyp6a8.…”
Section: Introductionmentioning
confidence: 98%
“…has also shown that Cyp6g1 is involved in organophosphate resistance through transgenically overexpressing the Accord element from a resistant strain (Hikone‐R) in D. melanogaster . Most recently, two P450s, Cyp6g1 and Cyp6g2 , have been shown to contribute to the metabolization of imidacloprid and are involved in conferring resistance to this insecticide in D. melanogaster …”
Section: Introductionmentioning
confidence: 99%
“…2016; Schmidt et al . 2017; Denecke et al . 2017), but have not yet been used to evaluate resistance to insecticides that have been and continue to be widely used, such as pyrethroids.…”
Section: Introductionmentioning
confidence: 99%